#TITLE_ALTERNATIVE# - HELLEYNA , FRIDA
This research is intended to learn about the application of remote sensing in order to get the information of coral reef condition at Pari Island - Thousand Islands based on the analysis of satellite image method, that is to say Lyzenga method. This research is also intended to study the condition of coral reef coverage percentage and its change at Pari Island -Thousand Islands through multi-spectral classification process of multi-temporal satellite images that had been transformed before by Lyzenga method. The satellite image data processed is Landsat ETM (Enhanced Thematic Mapper) satellite images of ThousandIslands for 2001 - 2002, also the in situ data of oceanographic condition and World Ocean Database (WOD), used as analysis material for oceanographic point of view. The Landsat ETM satellite image collected fromLembaga Antariksa dan Penerbangan Nasional (LAPAN) - Jakarta, the in situ data of oceanographic condition collected from Bappedalda DKI Jakarta - LAPI ITB, 2001, and the World Ocean Database downloaded fromNational Oceanography Data Center (NODC). The Lyzenga method applied in this research used tocorrect the depth factor, in order to get the clearer coral reef appearance at satellite image. So, its condition and change can be analyzed. The result from this research shows that thecoral reef condition at Pari Island - Thousand Islands from 2001 - 2002 is improved, which indicated by the live coral reef coverage increase with the rate of 0.1075 kmP2P/month or as big as 0.0085 %/month and by the dead coral reef coverage reduction with the rate of 0.0195 kmP2P/month or as big as 0.0195 %/month.